Obstetric racism experienced by black women: an integrative literature review (Research, Society and Development, 2022)
The present study aims to survey the data contained in the literature regarding obstetric racism associated with obstetric violence committed against black women, its impacts on maternal health, as well as expose the ways to combat this type of violence. This is a study based on the Integrative Literature Review (RIL) method, carried out in October 2021 in the Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Databases (BDENF) and in the Scientific Electronic Library Online (SciELO) and Medical Literature Analysis and Retrieval System Online (MEDLINE/PUBMED. Among the publications selected by the authors to compose the RIL of this study, 2 were published in 2016, 2 articles in 2020 and 3 articles in 2021. A total of 7 articles were identified. The discussions presented by the authors were described in two thematic categories. This study discusses racism linked to obstetric violence and the repercussions on maternal health and points out ways to combat obstetric racism a in order to guarantee the sexual and reproductive rights of black women. The present study proved to be relevant in addressing the issue of such social relevance, incorporating o the pertinent data contained in the studies selected for the discussion, showing the reality of black women victims of obstetric violence and the implications of these in their lives.